Chemical seeding via propanol plasma pretreatment for improving adhesion and properties of PECVD siloxane coatings on polymers. Issue 8 (8th December 2016) - Markanday, Jonathon F. S.; Charrault, Eric; Evans, Drew; Zuber, Kamil; Hall, Colin
Abstract : Siloxane coatings, in particular those deposited by plasma processes, find use as mechanical and environmental barriers for plastic substrates. This study highlights that a propanol‐based plasma pretreatment is not limited to only promoting greater adhesion of the siloxane to plastic. The optical and mechanical properties of graded siloxane coatings deposited onto plasma pretreated substrates are noticeably different to those deposited onto a pristine substrate, with the property change dependent on treatment time. Nanomechanical experiments have shown two distinct regions within the coating for the pretreated samples implying the pretreatment alters the seeding of the coating. It is proposed that the propanol plasma yields a substrate/chamber that is rich in hydroxyl groups which are subsequently incorporated into the growing siloxane coating. Abstract : Incorporation of hydroxyl groups at the start of the deposition via a propanol plasma pretreatment alter the seeding and growth of a thin film and give rise to mechanical and optical property changes. The plasma pretreated samples exhibited increased hardness and modulus and serve to illustrate how pretreatments may be used for alteration of thin film properties other than adhesion.